Implementation of Cognitive Theory in Developing Measurement Learning Multimedia for Deaf Students - I Made Suarsana; I Gde Wawan Sudatha; Gusti Ayu Mahayukti; I Wayan Edy Ari Suandana; I Gusti Putu Suharta (Jurnal Pendidikan dan Pengajaran, 2021)
The implementation of cognitive theory in multimedia development for deaf students (students with visual channels only) would be re-examined for its effectiveness. This study aimed to develop mathematics-learning multimedia based on cognitive theory for deaf students on "measurement". This development study adopted the 4D (define, design, develop, disseminate) study design. This study focused on determining the media feasibility based on expert validation, practicality trials, and effectiveness in the first year. The subjects of this study were 4 experts (content expert, learning design expert, media expert, and linguist), 2 teachers, and 7 students. The media feasibility data were collected with validation sheets, questionnaires, and tests. Furthermore, the data were analyzed using descriptive statistics. Based on the results, the feasibility level based on material experts, media experts, learning design experts, and linguists were 93.3%, 96.7%, 90%, and 93.3%, so it could be said that the developed multimedia met validity criteria. Based totally on the consequences, the multimedia practicality test for teachers and students were 95% and 93% respectively so that it could be said that multimedia met the practical criteria and the average percentage of student material mastery was 80.1% with passing grade of 71.4% so it could be said that multimedia met the effective criteria. Since the multimedia met the valid, practical, and effective criteria, it could be said that multimedia is feasible for learning.